(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Patriarchal social system is ruling the world hence there is a lack of power balance between females and males. Materials and Methods: A cross-sectional, descriptive study was carried out in different households in rural areas of Keraniganj Upazilla of Dhaka district between March 2016 and June 2016. The study population comprised of married women of reproductive age group (15-49 years) with a sample size of 201. Purposive sampling technique was applied. An interviewer administered structured questionnaire was developed and used after pre-testing to collect primary data. Data was collected by face to face interview of the respondents by the researchers during data collection period. After collection, data were checked and verified. Omissions and errors were corrected properly. Data were analyzed by using Social Package for the Social Sciences (SPSS version 22). Results: Most (71.70%) women did not take any precautionary measures to stop domestic violence. Only less than half of this category took precautionary measures. There was no statistical association between age and taking precautionary measures by the victims (P>0.05) as well as between occupation and taking precautionary measures by the victims (P>0.05). A large percentage (59.6%) of the victims tried to discuss the problem with their husbands to stop violence with the second largest category (30.8%) tried to get help from their members of paternal side. Maximum (29.5%) of the categories did not take any precautionary measures because of financial incapability. Lack of social security, personal helplessness, social taboo or stigma as a barrier for not taking any precautionary measures were 24.2% and 23.5%, 22.0% respectively. Conclusion: Women should be made aware of their rights and facilities available to combat the adverse effects of domestic violence. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 47-50